Land degradation as an object of forensic environmental expertise - Pazniak, Siarhei (Journal of the Belarusian State University. Ecology, 2023)
As a result of economic activity, the components of the environment are exposed to direct or indirect anthropogenic impact, as a result of which, as a rule, the functions, composition, properties and regimes of the soil change, its natural and economic significance decreases, i.e. soil degradation occurs. An analysis of investigative and expert practice shows that in court proceedings a significant part is occupied by materials related to land degradation as a result of violations of environmental legislation under Art. Art. 267, 269, 270 of the Criminal Code of the Republic of Belarus, art. art. 6.10, 6.11, 6.15 of the Code of the Republic of Belarus on Administrative Offenses.The article provides an example from the practice of conducting a forensic examination. As a result of illegal excavation of land in the coastal strip of the reservoir, the environment was harmed due to land degradation (including soil). In order to establish all the circumstances of the environmental offense and the truth in the case, in accordance with art. art. 226, 227, 228 of the Code of Criminal Procedure of the Republic of Belarus, a forensic environmental examination of objects of soil-geological origin was appointed. In connection with the prescription of the event under study and the fundamental change in the material situation on the land plots, the examination was carried out by studying the materials provided withthe decision to appoint an examination, analyzing the normative, normative-technical, special technical documentation in the field of environmental protection, situational analysis, comparing the results studies with the requirements of normative, normative-technical, special technical documentation and actual data that caused the occurrence of the event under study, as well as based on the results of an expert examination of the site of an environmental offense.In the course of the research, the circumstances of a specific environmental offense were established and answers were given to the questions of the body conducting the inquiry. It is shown that on the land plot provided for agricultural production, the fertile layer of the earth (soil) is not destroyed, its thickness corresponds to the average statistical values of the thickness of fertile horizons for soils of this type. The facts of land degradation (including soils), depletion, damage,destruction or other deterioration of their condition due to economic activities on the land plot have not been identified. As a result of agricultural production on the land plot, no harm was caused to the environment, since the original terrain did not change, land (soil) degradation was not detected, and damage to the fertile soil layer and grassy vegetation did not occur. When conducting business activities, violations of the rules of environmental protection were committed: clause 1.7, article 53, chapter 11 of the Water Code of the Republic of Belarus - arrangement of summer camps for farm animals within the boundaries of water protection zones, coastal strips and para. 4, part 1, article 89 of the Code of the Republic of Belarus on Land - pollution by production and consumption waste.
Keywords: forensic ecological examination of objects of soil-geological origin; land degradation; expert examination; fertile soil layer; unauthorized dump; littering; floodplain meadow; humus; environment; environmental damage